Evaluation of Birds Species Abundance and Diversity in Borgu Sector of Kainji Lake National Park, Nigeria (Global Journal of Science Frontier Research, 2019)
The study focused on bird's species abundance and diversity in Borgu sector of Kainji Lake National park Nigeria. Line transects were established in the collection of data on bird's species. Data collected were subjected to descriptive statistics (frequencies tables and percentages) as well as Simpson diversity index. The result on the checklist of birds obtained showed that there were 166 species belonging to 28 families. Results of the relative abundance of bird's species showed that Bubulcus ibis (77.88) and Ictinaetusmalayensis (0.29) had the highest and lowest relative abundance respectively. The result of the Simpson diversity index (0.939) of bird species by families showed that Ardeidae (593) and family Sturnidae (392) had the highest and lowest number of bird's species respectively. Environmental education (conservation, production and enrichment) campaign should be carried out on the status of birds and other components of the ecosystem to boost the tourism potentials of the park.
Keywords: birds2019; species; list; abundance; diversity